A new modular approach to nanoassembly: stable and addressable DNA nanoconstructs via orthogonal click chemistries. - Gerrard, SR; Hardiman, C; Shelbourne, M; Nandhakumar, I; Nordén, B; Brown, T (2012)
Thermodynamic instability is a problem when assembling and purifying complex DNA nanostructures formed by hybridization alone. To address this issue, we have used photochemical fixation and orthogonal copper-free, ring-strain-promoted, click chemistry for the synthesis of dimeric, trimeric, and oligomeric modular DNA scaffolds from cyclic, double-stranded, 80-mer DNA nanoconstructs. This particular combination of orthogonal click reactions was more effective for nanoassembly than others explored. The complex nanostructures are stable to heat and denaturation agents and can therefore be purified and characterized. They are addressable in a sequence-specific manner by triplex formation, and they can be reversibly and selectively deconstructed. Nanostructures utilizing this orthogonal, chemical fixation methodology can be used as building blocks for nanomachines and functional DNA nanoarchitectures.